Giving information to family members of patients in the intensive care unit: Iranian nurses' ethical approaches. - Mansoureh A Farahani (Journal of Medical Ethics and History of Medicine, 2015)
Receiving information related to patients hospitalized in the intensive care unit is among the most important needs of the family members of such patients. When health care professionals should decide whether to be honest or to give hope, giving information becomes an ethical challenge We conducted a research to study the ethical approaches of Iranian nurses to giving information to the family members of patients in the intensive care units. This research was conducted in the intensive care units of three teaching hospitals in Iran. It employed a qualitative approach involving semi-structured and in-depth interviews with a purposive sample of 12 nurses to identify the ethical approaches to giving information to family members of the intensive care unit patients. A conventional content analysis of the data produced two categories and five subcategories. The two categories were as follows: a) informational support, and b) emotional support. Informational support had 2 subcategories consisting of being honest in giving information, and providing complete and understandable information. Emotional support in giving information had 3 sub-categories consisting of gradual revelation, empathy and assurance. Findings of the study indicated that ethical approaches to giving information can be in the form of either informational support or emotional support, based on patients' conditions and prognoses, their families' emotional state, the necessity of providing a calm atmosphere in the ICU and the hospital, and other patients and their families' peace. Findings of the present study can be used as a basis for further studies and for offering ethical guidelines in giving information to the families of patients hospitalized in the ICU.